Pengaruh Sanksi Perpajakan, Tax Amnesty, dan Pemahaman Perpajakan terhadap Kepatuhan Wajib Pajak: - Arifin, Zumam; Subiyanto, Bambang; Digdowiseso, Kumba (LPPM Institut Nasional Laa Roiba Bogor, 2024)
This study aims to examine the effect of tax sanctions, tax amnesty, and understanding of taxation on taxpayer compliance. The population in this study were all taxpayers who were registered at the Pratama Kebayoran Baru Satu Jakarta Selatan II Tax Service Office (KPP). Sampling in this study used the technique of distributing questionnaires directly to taxpayers in hardcopy and google form which found as many as 118 respondents. Processing and testing of data using the SPSS (Statistical Package for the Social Science) program version 25. The results obtained in this study indicate that tax sanctions, tax amnesty, and understanding of taxation have a positive and significant effect on taxpayer compliance. Keywords: tax sanctions, tax amnesty, understanding of taxation, taxpayer compliance.